The influence of cycling on lower limb movement and muscle activation during running in triathletes - Chapman, A. R.; Vicenzino, B.; Blanch, P.; Dowlan, S.; Hodges, P. W. (ISB Congress, 2006)
This study investigated the influence of the triathlon transition on movement and muscle recruitment in highly trained triathletes using a protocol designed to provide the triathletes with exposure to cycling without causing fatigue.